2004
DOI: 10.1080/02652030410001712484
|View full text |Cite
|
Sign up to set email alerts
|

Formation of semicarbazide (SEM) in food by hypochlorite treatment: is SEM a specific marker for nitrofurazone abuse?

Abstract: Semicarbazide (SEM) is considered to be a characteristic protein-bound side-chain metabolite of the banned veterinary drug nitrofurazone. It is therefore used as a marker for nitrofurazone abuse. Recently, there has been concern about other sources of SEM in tissue samples, which are not linked to the illegal use of nitrofurazone. The present studies have shown that SEM can occur naturally, e.g. in algae, shrimps and eggs, and is formed from natural substances, e.g. arginine and creatine. A significant formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 14 publications
2
68
0
Order By: Relevance
“…The formation of SEM during the baking of bread (Becalski et al, 2004(Becalski et al, , 2006 and flour-coated poultry products (Hoenicke et al, 2004) was also confirmed when the use of azodicarbonamide as an additive in flour was examined. SEM formation has also been observed in samples such as carrageen (a seaweed extract used as a food additive), starch and egg white powder treated with hypochlorite solutions containing 12% active chlorine (Hoenicke et al, 2004).…”
Section: Sources Of Nitrofuran and Semicarbazide Contaminationmentioning
confidence: 89%
See 2 more Smart Citations
“…The formation of SEM during the baking of bread (Becalski et al, 2004(Becalski et al, , 2006 and flour-coated poultry products (Hoenicke et al, 2004) was also confirmed when the use of azodicarbonamide as an additive in flour was examined. SEM formation has also been observed in samples such as carrageen (a seaweed extract used as a food additive), starch and egg white powder treated with hypochlorite solutions containing 12% active chlorine (Hoenicke et al, 2004).…”
Section: Sources Of Nitrofuran and Semicarbazide Contaminationmentioning
confidence: 89%
“…SEM formation has also been observed in samples such as carrageen (a seaweed extract used as a food additive), starch and egg white powder treated with hypochlorite solutions containing 12% active chlorine (Hoenicke et al, 2004). Hypochlorite is commonly used for carrageen bleaching or water disinfection and also as a disinfectant during egg breaking procedures (de la Calle and Anklam, 2005).…”
Section: Sources Of Nitrofuran and Semicarbazide Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of SEM in carrageenan (Hoenicke et al, 2004) demonstrated to these researchers that it was not possible to differentiate between SEM resulting from Nitrofuran abuse; SEM occurring naturally or by bleaching processes involved in producing semi-refined carrageenan (PES). Subsequently tests demonstrated that SEM had weak mutagenic activity and posed no risk to humans in the amounts likely to be consumed (Abramsson-Zetterberg et al, 2005;AFC Panel, 2005;Hoenicke et al, 2006;Hoenicke et al, 2004).…”
Section: Case III the 'Tobacman' Controversymentioning
confidence: 99%
“…These covalently-bound metabolites are used as marker residues for detecting the illicit use of nitrofurans in animal production. It should be noted that the metabolite semicarbazide (SEM) has been shown not to be an unambiguous marker for abuse of the nitrofuran drug nitrofurazone because the semicarbazide molecule may occur from other sources (Hoenicke, et al, 2004;Sarnsonova, et al, 2008;Bendall, 2009). …”
Section: (A) Dioxinsmentioning
confidence: 99%